Assessment of Nonresearch Industry Payments to Otolaryngologists in 2014 and 2015. (13th February 2018) - Pathak, Neil; Fujiwara, Rance J. T.; Mehra, Saral
Abstract : Objective: To characterize, describe, and compare nonresearch industry payments made to otolaryngologists in 2014 and 2015. Additionally, to describe industry payment variation within otolaryngology and among other surgical specialties. Study Design: Retrospective cross‐sectional database analysis. Setting: Open Payments Database. Subjects and Methods: Nonresearch payments made to US otolaryngologists were characterized and compared by payment amount, nature of payment, sponsor, and census region between 2014 and 2015. Payments in otolaryngology were compared with those in other surgical specialties. Results: From 2014 to 2015, there was an increase in the number of compensated otolaryngologists (7903 vs 7946) and in the mean payment per compensated otolaryngologist (1096 vs 1242), as well as a decrease in the median payment per compensated otolaryngologist (169 vs 165, P =. 274). Approximately 90% of total payments made in both years were attributed to food and beverage. Northeast census region otolaryngologists received the highest median payment in 2014 and 2015. Compared with other surgical specialists, otolaryngologists received the lowest mean payment in 2014 and 2015 and the second‐lowest and lowest median payment in 2014 and 2015, respectively. Conclusion: The increase in the mean payment and number of compensated otolaryngologists can be explained by normal annual variation, stronger industry‐otolaryngologist relationships, or improved reporting; additional years of data and improved public awareness of the Sunshine Act will facilitate determining long‐term trends. The large change in disparity between the mean and median from 2014 to 2015 suggests greater payment variation. Otolaryngologists continue to demonstrate limited industry ties when compared with other surgical specialists.